Nutritional and microbial quality of streetfood chicken (Gallus gallus) proven in Los Baños, Philippines. - Barrion, A. S. A. (Compendium of Human Ecology Researches in the Philippines, 2003)
One of the favorite street foods in the Philippines is the deep fried chicken proventiculus called chicken proven. The nutrient content, free fatty acids. and peroxide values of chicken proven at various stages of preparation were determined. Raw proven had 39.08% crude protein, 25.59% carbohydrates, 25.59% crude fat, 0.61% crude fiber, and 51.50 kcal per 100 g. Newly cooked proven increased in its crude fat (31%), fiber (131%), carbohydrates (21%), and caloric (935%) contents but decreased in its crude protein (26%), calcium (21%), phosphorus (4%), iron (44%), ash (32%), and moisture (56%) contents. The slight changes in the nutrient content of the stored cooked proven were only due to leaching out of fat and corresponding changes in percentage composition. Significant reduction in free fatty acids with a corresponding significant increase in pH was also noted. Peroxides were not observed in all chicken proven samples. Assessment of the microbial quality of the chicken proven at different stages of preparation indicated the risk of contamination with pathogenic food-borne microbes such as coliform, Staphylococcus and Salmonella. Deep fat frying of proven destroyed majority of these microorganisms but storage at ambient temperature caused microbial growth. The presence of these pathogenic microbes in cooked proven and their subsequent growth during storage are the critical control points. Microbial contamination of proven can be reduced through the practice of personal hygiene, employing standard cooking temperature (171-185°C) and time (10-15 mins) and cooking as ordered.